Electricity sector in the Galapagos Islands: Current status, renewable sources, and hybrid power generation system proposal - Llerena-Pizarro, Omar R. [UNESP]; Micena, Raul Pereira [UNESP]; Tuna, Celso Eduardo [UNESP]; Silveira, José Luz [UNESP] (Elsevier, 2019)
The electricity sector in the Galapagos Islands is heavily dependent on fossil fuels for electricity generation but only a few renewable sources are used for such a purpose in this archipelago. Therefore, this work aims to present the current status of its electricity sector and show estimates for the upcoming years, discuss exploited and unexploited renewable resources, and put forward a proposal for a hybrid system to generate renewable power. Currently, thermoelectric power plants run on diesel are the main source of electricity generation in the archipelago due to supplying 85% of the total power installed in the islands (27.6 MW), and the remaining 15% (7.3 MW) is from renewable sources, such as the wind (10.8%), sun (4.1%), and vegetable oils (0.1%). In the upcoming years, there will be a growth in the use of these renewable resources if an additional capacity of 28.5 MW is installed. The gross electric output generated by this sector in the last twelve months (March 2017 - February 2018) was 53.80 GWh, which has allowed a return on revenues of over five million dollars at an average cost of US $0.10/kWh. Based on the existing renewable resources in the Galapagos Islands, the implementation of a hybrid solar/biogas power generation system is an attractive alternative to support the zero-fossil fuel initiative, diversify the energy matrix, and promote local development. However, sustainable development policies, energy efficiency programs and foreign investment funds to carry out new projects are required to ensure a bright future for the electricity sector in the Galapagos.
Keywords: Electricity generation; Galapagos; Renewable energy; Solar/biogas power plant